2016
DOI: 10.14202/vetworld.2016.1238-1241
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hepcidin and oxidant/antioxidant status in calves with suspected neonatal septicemia

Abstract: Aim:This study has been conducted for the purpose of determining serum hepcidin, total antioxidant status (TAS), total oxidant status (TOS), and Fe levels in calves with suspected neonatal septicemia before and after treatment and the clinical significance of hepcidin in calves with suspected neonatal septicemia.Materials and Methods:The study material consisted of 15 calves of different ages and sexes brought to the Training, Research and Application Center at the Kafkas University Faculty of Veterinary Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
6
0
3
Order By: Relevance
“…The increase of ROS causes cellular oxidative damage. In this case, inhibition of protein synthesis leads to occurrence of DNA damage and the formation of cellular death (7,13,23,27,28). In this study which was presented in parallel with results of Bozukluhan et al (5), TOC was higher (P < 0.001) and TAC was lower in FMD group compared to control group.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of ROS causes cellular oxidative damage. In this case, inhibition of protein synthesis leads to occurrence of DNA damage and the formation of cellular death (7,13,23,27,28). In this study which was presented in parallel with results of Bozukluhan et al (5), TOC was higher (P < 0.001) and TAC was lower in FMD group compared to control group.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the oxidative stress index increased. In many studies, it has been reported that oxidative stress occurs in diarrhea and septicemia that develops as a result [39][40][41]. When cells are exposed to oxidative stress, they increase the activity and expression of antioxidant enzymes to protect them from damage caused by free radicals [42].…”
Section: Discussionmentioning
confidence: 99%
“…Hepcidin also helps host defense due to its direct antimicrobial properties (8,23). Erkilic et al (7), reported that serum hepcidin levels were very high in calves suspected of septicemia, and these levels decrease drastically after treatment. In our previous study on 56 cattle with single and dual infection (BHV-1, BVDV), hepcidin levels were compared.…”
Section: Discussionmentioning
confidence: 99%